Enhancing Diabetic Foot Ulcer Healing: The Role of Channa striata Extract Nutrition in Accelerating Inflammatory, Proliferative, and Maturation Phases - Idramsyah, Idramsyah; Dahrizal, Dahrizal; Ruran, Marina; Nair, Harikrisna K. R. (Universitas Muhammadiyah Yogyakarta, 2024)
Background: Diabetic foot ulcers pose a severe complication for individuals with diabetes mellitus, necessitating effective therapeutic support such as albumin nutrition throughout the wound healing process. Derived from Channa striata, a commonly consumed source of albumin in Indonesia, this extract can potentially expedite wound healing.Objective: This study aims to evaluate the efficacy of Channa striata extract nutrition in accelerating the inflammatory, proliferative, and maturation phases of diabetic foot ulcer healing.Methods: This quantitative study employed a pra-experimental design using a single-group pretest-posttest approach. The study involved 30 diabetic patients who were administered a daily dose of 550 grams of Channa striata extract over four weeks. The Bates Jensen Assessment Tool (BWAT) assessed wound progress.Results: Results revealed that the average participant age was 60.2 years, with an average diabetic history of seven years. The average wound duration was 8.7 weeks; 66.7% of the participants were female; 70% had Non-Insulin Dependent Diabetes Mellitus (NIDDM); and 56.7% were at stage IV. The study found a significant difference in BWAT scores before and after the administration of Channa striata extract in diabetic foot ulcer patients.Conclusion: This study supports the effectiveness of Channa striata extract as an adjunct therapy in expediting the wound-healing phases in diabetic foot ulcers.